The efficacy of rituximab in treatment of childhood steroid resistant and steroid dependent nephrotic syndrome: a systematic review and Meta-analysis - Hamid Mohammadjafari; Ahmadali Nikibakhsh; Abbas Alipour (Mazandaran University of Medical Sciences, 2013)
Corticosteroid resistant and dependent nephrotic syndrome in children is a challenge and there are some difficulties in treating such patients. We reviewed the current studies that evaluated therapeutic role of a relatively new immunosuppressive drug "rituximab" in reducing proteinuria and reduction of relapse rate in less than 16 year old patients with non-responsive or steroid dependent nephrotic syndrome. We searched Medline, Embase, web of science and Cochrane library with appropriate keywords and conducted the complete remission, relapse rate and the mean number of relapses 12 months after therapy on Meta-analysis. We put the data on two different subgroups steroid resistant nephrotic syndrome and steroid dependent or frequent relapser nephrotic syndrome. In Steroid Resistant Nephrotic syndrome children, the complete remission was 0.27 (0.2- 0.34). In Steroid Dependent Nephrotic syndrome patients, the overall standard mean differences of mean number of relapses 12 months after treatment in pooled four studies (56 cases) was 2.63 (2.03, 3.24). In these dependent patients, the data on relapse rate after treatment pooled on 6 studies (162 cases) and yield to the rate of 0.42 (0.15, 0.69) with the range of 0.09 to 0.83. In conclusion, Rituximab is a reasonable therapy for Steroid Dependent and Steroid Resistant Nephrotic syndrome children. In view of paucity of randomized data, we suggest to perform newer controlled multicenter studies.